EFEKTIVITAS KOMUNIKASI INTERPERSONAL HOST SHOPEE LIVE TERHADAP PERILAKU KONSUMTIF GENERASI Y - Stiawanty, Rita; Andrini, Susi (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The goal of this study is to assess how the quality of interpersonal communication by Shopee Live hosts impacts the consumption patterns of Generation Y. This study employs a descriptive quantitative methodology. Data collection was conducted using a closed-ended questionnaire distributed to one hundred Shopee Live respondents, selected based on calculations using Slovin’s formula. The questionnaire was administered via Google Forms, and the data was processed using SPSS version 26. Data analysis involved descriptive analysis, normality testing, simple linear regression testing, and hypothesis testing. The findings from this research show that the alternate hypothesis (Ha) is supported, revealing a favorable impact of effective interpersonal communication by Shopee Live hosts on the consumer behavior of Generation Y. The coefficient of determination is calculated at 53.6%, indicating a significant correlation. The unexplored factors in this study account for the remaining 46.4% of the influences on consumer behavior. Therefore, it can be stated that the effectiveness of interpersonal communication by hosts has a moderate impact on the consumptive behavior of Generation Y, as the coefficient of determination is above 50%. This research provides benefits for practitioners as a reference in understanding the consumptive behavior of Generation Y in the online shopping environment of Shopee Live. Additionally, it serves as a study material and foundation for future research, particularly in the field of communication studies, for other researchers interested in similar topics.